Rituximab induces rapid blood repopulation by CLL cells mediated through their release from immune niches and complement exhaustion - Borsky, Marek; Hrabcakova, Viera; Novotna, Jitka; Brychtova, Yvona; Doubek, Michael; Panovska, Anna; Muller, Petr; Mayer, Jiri; Trbusek, Martin; Mraz, Marek (Leukemia research, 2021)
The in vivo rituximab effects in B cell malignancies are only partially understood. Here we analyzed in a large chronic lymphocytic leukemia (CLL) cohort (n = 80) the inter-patient variability in CLL cell count reduction within the first 24 h of rituximab administration in vivo, and a phenomenon of blood repopulation by malignant cells after anti-CD20 antibody therapy. Larger CLL cell elimination after rituximab infusion was associated with lower pre-therapy CLL cell counts, higher CD20 levels, and the non-exhausted capacity of complement-dependent cytotoxicity (CDC). The absolute amount of cell-surface CD20 molecules (CD20 density x CLL lymphocytosis) was a predictor for complement exhaustion during therapy. We also describe that a highly variable decrease in CLL cell counts at 5 h (88 %-2%) following rituximab infusion is accompanied in most patients by peripheral blood repopulation with CLL cells at 24 h, and in ∼20 % of patients, this resulted in CLL counts higher than before therapy. We provide evidence that CLL cells recrudescence is linked with i) CDC exhaustion, which leads to the formation of an insufficient amount of membrane attack complexes, likely resulting in temporary retention of surviving rituximab-opsonized cells by the mononuclear-phagocyte system (followed by their release back to blood), and ii) CLL cells regression from immune niches (CXCR4dimCD5bright intraclonal subpopulation). Patients with major peripheral blood CLL cell repopulation exhibited a longer time-to-progression after chemoimmunotherapy compared to patients with lower or no repopulation, suggesting chemotherapy vulnerability of CLL cells that repopulate the blood.
Keywords: protinádorové látky imunologicky aktivní; Peripheral blood repopulation; Chronic lymphocytic leukemia/CLL; cytotoxicita imunologická; lidé; komplement; Complement; Antineoplastic Agents, Immunological; Cytotoxicity, Immunologic; rituximab; chronická lymfatická leukemie; Follow-Up Studies; Recrudescence; Humans; následné studie; Rituximab; Complement System Proteins; Leukemia, Lymphocytic, Chronic, B-Cell